If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying X(40 + x) = 6000 (40 * X + x * X) = 6000 (40X + xX) = 6000 Solving 40X + xX = 6000 Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Reorder the terms: -6000 + 40X + xX = 6000 + -6000 Combine like terms: 6000 + -6000 = 0 -6000 + 40X + xX = 0 The solution to this equation could not be determined.
| -33+53= | | 8x+5z=5+5y | | 7=x(-13+x)-11+6x | | 4x^2-16x=-y^2+10y-40 | | 9x+4x+3+8=4x+3x+8x | | lnx=-1/5 | | 5y-4=13y+68 | | 4x+22=3+7x-8 | | 1/3(x-4)^=1 | | (2000(1-x/60)^2)/x | | 6+1-2x=5x+x-7 | | (5x+20)(3x+66)= | | 6x+7z=4+5y | | Ydy/dx-e^x=O | | 7(2x-9)=43 | | (2s-3)+s+(3s-30)=207 | | r+21=15 | | 5x-3=12+x-1+2 | | 40+2*5= | | k^4-100k=0 | | 3/2x-1/3x | | 0=-16t^2+4.5t | | 16c^2-70c+49=0 | | 1/2=d/4 | | 8-x=3x+8 | | 3x+1x=36 | | y/50=-21 | | 2x^4-13x^2+17=0 | | p/2.3=4 | | a+b=19 | | x/5.3=0.7 | | 80=-8k |